PEMBERDAYAAN MASYARAKAT DAN MODERASI BERAGAMA DI DESA TEBING LINGGAHARA KECAMATAN BILAH BARAT: (Implementasi Manajemen Partisipatif) - Saragih, Afria Ulfa; Muktarruddin; Ritonga, Fahmi Adha (Jurnal Dakwah Tabligh, 2023)
This study aims to examine the implementation of participatory management in community empowerment and religious moderation in Tebing Linggahara Village, Bilah Barat District. This study uses a qualitative approach with a case study design. Data collection techniques include observation, interviews, and documentation. Data analysis techniques include data condensation, data display, conclusion drawing, or verification. The results of the study show that: (1) the condition of community empowerment and religious moderation in the village is still unsatisfactory, (2) the implementation of participatory management in community empowerment and religious moderation in the village is still not optimal, (3) there are some challenges and opportunities in the implementation of participatory management in the village. This study contributes theoretically and practically to the development of knowledge, especially in the fields of participatory management, community empowerment, and religious moderation. This study also provides input for the government, community, and other stakeholders in formulating appropriate strategies and policies to improve the welfare and harmony of Tebing Linggahara Village.